Hadith #4343 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ady bin 'Ady bin 'Umayra عدي بن عدي بن عميرة; al-Mughira bin Ziyad al-Bjly المغيرة بن زياد البجلي أبو هشام (Sunan Abi Dawud)
When we were around the Messenger of Allah (ﷺ), he mentioned the period of commotion (fitnah) saying: When you see the people that their covenants have been impaired, (the fulfilling of) the guarantees becomes rare, and they become thus (interwining his fingers). I then got up and said: What should I do at that time, may Allah make me ransom for you? He replied: Keep to your house, control your tongue, accept what you approve, abandon what you disapprove, attend to your own affairs, and leave
Grade: Hasan Sahih

Hadith #4344 - Sunan Abi Dawud - Ady bin 'Ady bin 'Umayra عدي بن عدي بن عميرة; Musa bin Nafi', Abu Shahab al-Hanat موسى بن نافع الأسدي أبو شهاب الحناط (Sunan Abi Dawud)
The Prophet (ﷺ) said: The best fighting (jihad) in the path of Allah is (to speak) a word of justice to an oppressive ruler.
Grade: Sahih